Pendampingan Penyusunan Asesmen Diagnostik pada Sekolah Dasar di Kota Samarinda: Assistance in Preparing Diagnostic Assesment on Elementary School in Samarinda - Tindangen, Makrina; Fendiyanto, Petrus; Hardoko, Aloysius (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The Mobilizing Organization Program is a community empowerment program through government support to improve the competence of teachers and school principals as evidenced by increased student learning outcomes. This program was attended by 127 community organizations from all over Indonesia as partners of the Ministry of Education, Culture, Research, and Technology, which was appointed as the implementer of this program, and one of them was the Yayasan Kasih Sejati Kalimantan. The activity period for this program starts from February – June 2023. The targets of this activity are school principals and elementary school teachers in the city of Samarinda, totaling 20 schools. This activity aims to provide understanding to teachers and school principals about diagnostic assessments which are part of independent curriculum learning. The implementation of this activity is divided into three stages, namely preparation, training implementation, monitoring, and evaluation. The material provided in this activity includes cognitive and non-cognitive diagnostic assessments, stages of diagnostic assessments, time to carry out diagnostic assessments, and examples of cognitive and non-cognitive diagnostic assessments. Apart from preparing a diagnostic assessment, participants are also required to complete a worksheet prepared by the resource person during the training. In general, participants’ perceptions of the assistance activities in preparing diagnostic assessments gave a very good response. Participants can also implement the preparation of diagnostic assessments in their respective schools, this is based on the results of monitoring and evaluation.